Sustainable Farming Education: A Case of Non-Formal Education At Lembaga Pengembangan Pertanian Nahdlatul Ulama (Nahdlatul Ulama Agricultural Development Institute) - M. Fatah; Giyoto; Islah (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2025)
To mitigate the adverse effects of modern farming systems on natural resources, we need sustainable agriculture immediately. Nahdlatul Ulama (NU), the largest Islamic group in Indonesia, plays a strategic role in raising awareness and encouraging sustainable farming practices through informal education. This study investigates NU's non-formal education initiative designed to promote the shift from exploitation to conservation within the agricultural sector. Utilizing a qualitative methodology rooted in empirical analysis and literature review, the study investigates the integration of Islamic values, indigenous knowledge, and agroecological principles into farmer empowerment curricula through collaborations between pesantrens and the Nahdlatul Ulama Agricultural Development Institute (LPPNU). The results underscore the pivotal function of NU's non-formal education in augmenting farmers' ecological awareness, fostering the implementation of organic farming practices, and bolstering community-oriented food security. But there are still problems, like not having enough access to resources and not having enough policy support. In summary, NU's non-formal education programs provide a promising framework for promoting sustainable agriculture based on Islamic principles and local cultural contexts. The study offers policy recommendations for the incorporation of ecological and social sustainability into educational and agricultural development in Indonesia.